The teacher of Computer science: specialization or a speciality (Journal of Information Technologies in Education (ITE), 2009)
The article is devoted to the aggravation of problem of future teachers of computer science training for comprehensive school from the point of view of methodical and organizational questions. Training impossibility of competent expert within the limits of an academic load, which is assigned for specializations, demands the refusal of specialization: Computer Science in institution of higher education for training direction Mathematics* and Physics*, also puts a question about the necessity of opening of new direction of students training, exactly Computer Science*.
Keywords: Computer Science training technique; teacher of Computer Science